Effects of dopamine agonists on neuropsychiatric symptoms of Parkinson's disease - Rektorová, Irena (Neuro-degenerative diseases, 2010)
The efficacy of dopamine (DA) agonists in the treatment of motor symptoms of Parkinson's disease (PD) has been clearly demonstrated. It has also been documented that DA agonists may have both a positive and a negative impact on neuropsychiatric symptoms in PD patients. This paper will focus on the effects of DA agonists on depressive and cognitive symptoms of PD.
Keywords: radioizotopy jodu; Male; klinické zkoušky jako téma; kognitivní poruchy; Aged; mužské pohlaví; senioři; deprese; radioisotopová scintigrafie; Iodine Radioisotopes; Neuropsychological Tests; lidé; ženské pohlaví; Humans; Tropanes; Cognition Disorders; tropany; Radionuclide Imaging; neuropsychologické testy; agonisté dopaminu; psychiatrické posuzovací škály; Female; Parkinsonova nemoc; Depression; lidé středního věku; Parkinson Disease; Psychiatric Status Rating Scales; Dopamine Agonists; Middle Aged; Clinical Trials as Topic